2020
DOI: 10.1021/acsaem.0c00867
|View full text |Cite
|
Sign up to set email alerts
|

Elucidating the Sodiation Mechanism in Hard Carbon by Operando Raman Spectroscopy

Abstract: Operando microbeam Raman spectroscopy is used to map the changes in hard carbon during sodiation and desodiation in unprecedented detail, elucidating several important and unresolved aspects of the sodiation mechanism. On sodiation a substantial, reversible decrease in G-peak energy is observed, which corresponds directly to the sloping part of the voltage profile and we argue can only be due to steady intercalation of sodium between the turbostratic layers of the hard carbon. Corresponding reversibility of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
65
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 69 publications
(77 citation statements)
references
References 65 publications
5
65
1
Order By: Relevance
“…For the main sloping region of sodiation (40.1 V vs. Na + /Na), both peaks are found to become broader, while the D-peak is gradually shifting to a higher wavenumber (blue shift), meaning that in this region, Na + ions are forming chemical bonding with atoms at in-plane defect sites such as carbon vacancies, substitutional impurities, interstitial impurities. 55,56 These findings can also support that the longest sloping region in the GCD curve of L700 results from the interaction of Na + ions with defect sites. The position of the G-peak remains almost unchanged during the main sloping region of sodiation, suggesting no significant electrochemical interaction of Na + ions with the graphitic bands since the G-peak position and width are highly sensitive to electron or ion doping.…”
Section: Fundamental Mechanism Insights Into Interfacial Phenomena and Deposition Behavioursupporting
confidence: 60%
See 1 more Smart Citation
“…For the main sloping region of sodiation (40.1 V vs. Na + /Na), both peaks are found to become broader, while the D-peak is gradually shifting to a higher wavenumber (blue shift), meaning that in this region, Na + ions are forming chemical bonding with atoms at in-plane defect sites such as carbon vacancies, substitutional impurities, interstitial impurities. 55,56 These findings can also support that the longest sloping region in the GCD curve of L700 results from the interaction of Na + ions with defect sites. The position of the G-peak remains almost unchanged during the main sloping region of sodiation, suggesting no significant electrochemical interaction of Na + ions with the graphitic bands since the G-peak position and width are highly sensitive to electron or ion doping.…”
Section: Fundamental Mechanism Insights Into Interfacial Phenomena and Deposition Behavioursupporting
confidence: 60%
“…The position of the G-peak remains almost unchanged during the main sloping region of sodiation, suggesting no significant electrochemical interaction of Na + ions with the graphitic bands since the G-peak position and width are highly sensitive to electron or ion doping. 55 When the potential is close to 0 V vs. Na + /Na, the decrease of G-peak View Article Online position can be measured concomitant with an increase in its width because Na + ions are interacting with graphitic bands in this region. The transfer of charge from the sodium atoms to p* antibonding orbitals of carbons affects the length of the C-C bonds.…”
Section: Fundamental Mechanism Insights Into Interfacial Phenomena and Deposition Behaviourmentioning
confidence: 99%
“…It is well known that Li + ions intercalate into the graphite structure forming Li x C 6 , which generally results in a shift to the lower binding energy of the C=C bond [37] . Likewise, it has been recently reported that also the insertion of Na + ions into the turbostratically layered pseudo‐graphitic nano domain (TLPG‐ND) of HCs causes a shift of the peak position [21] . Therefore, selecting the pseudo‐graphitic‐like peak as a reference for the binding energy calibration would lead to unprecise peak attribution.…”
Section: Methodsmentioning
confidence: 99%
“…Despite the promising properties, several disadvantages affect the performance of HC as anode material, such as the poor initial coulombic efficiency (ICE), the low power performance, and the instability of the solid electrolyte interphase (SEI) [17,18] . For this reason, a renewed attention has been recently focused towards the fundamental understanding of the sodiation mechanism, aiming at elucidating a direct relation among structural properties of HC and its electrochemical behavior especially by employing operando characterization methods [10,19–22] . However, the controversial nature of the HC structure hinders a comprehensive understanding of the structure‐function correlation [20,22–29] …”
Section: Introductionmentioning
confidence: 99%
“…[ 99 ] For graphite anodes in LIBs, analysis of the G‐peak has been used during operando and in situ charging studies to reveal that the intercalation occurs in distinct steps forming high stage graphite intercalation compounds (where ‘stage’ refers to the number of graphite layers between each of intercalant) eventually forming stage 1 LiC 6 at full charging. [ 100–102 ] For hard carbon‐based electrodes, by fitting the G‐peak position and width with doping, it has been shown that Na‐ion intercalation is incremental (and associated with the sloping part of the voltage profile), [ 103,104 ] similar to the incremental charging found in single to few layer graphene. [ 105 ] However, the lateral resolution limit of Raman scattering is far larger than for AFM, being limited by the diffraction limit of light, thus blind to the detailed atomic‐scale changes that can occur.…”
Section: Ec‐afm For the Understanding Of Libs And Their Materialsmentioning
confidence: 99%